1992
DOI: 10.1104/pp.98.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Rhodamine 123 Fluorescence during Modulation of the Membrane Potential in Plant Mitochondria

Abstract: The fluorescent dye rhodamine 123, which selectively accumulates in mitochondria based on the membrane potential, was used with flow cytometry to evaluate variations in activity of mitochondria isolated from plant tissues. In the presence of succinate and ATP, potato (Solanum tuberosum L.) tuber mitochondrial activity was affected by metabolic inhibitors and compounds that modify the membrane potential. The more uniform the mitochondrial population, the higher the observed membrane potential. The reactive popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
6
22
0
Order By: Relevance
“…In contrast with the most common observations with whole cells, the FALS seems to reflect the density (internal structure) of the particles rather than their size in subcellular particles. A similar phenomenon was encountered in the case of both animal and plant mitochondria (27,30).…”
Section: Cytologysupporting
confidence: 73%
“…In contrast with the most common observations with whole cells, the FALS seems to reflect the density (internal structure) of the particles rather than their size in subcellular particles. A similar phenomenon was encountered in the case of both animal and plant mitochondria (27,30).…”
Section: Cytologysupporting
confidence: 73%
“…Methods have been developed in recent years based on plant protoplast, nuclear and pollen suspensions (Brown and Bergounioux, 1989;Galbraith et al, 1983Galbraith et al, , 1984Harkins and Galbraith, 1987). Current applications of flow cytometry to plant cells include DNA and RNA analysis, detection of transgene expression, karyotyping, cell counting, studies of chloroplasts, cell membranes and cell wall regeneration, evaluation of mitochondrial activity, measurement of secondary metabolite accumulation, and selection of particular cells or sub-cellular organelles of interest (Adamse, 1990;Bergounioux et al, 1992;Conia and Muller, 1989;Galbraith, 1989;Galbraith et al, 1995;Nicoloso et al, 1994;Petit, 1992;Sakamoto et al, 1994;Schröder and Petit, 1992). Methods for BrdU labeling of plant cells were first described by Levi et al (1987) to determine the proportion of S-phase cells in pea root meristems using microscope photometry.…”
Section: Introductionmentioning
confidence: 99%
“…Plant mitochondrial heterogeneity depends on plants species, tissue, ontogeny, cellular type, and energetic state of mitochondria and they are often associated with other organelles and structures (Logan and Leaver, 2000). Contrary to TEM, confocal microscopy: (1) eliminates interferences from chloroplasts regardless of mitochondrial localization within the cytoplasm; (2) provides a global three-dimensional cell view so that mitochondrial morphology and mitochondrial-in-cell position is considered; and (3) Rhodamine 123 stains only metabolically functional mitochondria (Petit, 1992).…”
Section: Analysis Of Cell and Organelle Parametersmentioning
confidence: 99%
“…Active mitochondria were stained by using Rhodamine 123 (Sigma-Aldrich), which selectively accumulates in mitochondria based on the membrane potential (Petit, 1992). Fresh tissue samples were incubated for 12 min in 250 mM Rhodamine 123 (Sigma Aldrich) at 37°C in the dark (previous trial studies indicated that less incubation time stained less brightly mitochondria and more incubation time quickly toxified tissues, and the staining rapidly disappeared).…”
Section: Analysis Of Cell and Organelle Parametersmentioning
confidence: 99%